PENGEMBANGAN PEMBANGUNAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) PISANG KAPIK PADA MASA PANDEMI COVID-19 DI KOTA BUKITTINGGI - Arliman S, Laurensius (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research investigates the development of Micro, Small, and Medium Enterprises (MSMEs) in the banana chip industry during the COVID-19 pandemic in Bukittinggi City. MSMEs play a strategic role in increasing income, employment opportunities, poverty alleviation, and expanding job markets in Indonesia. The reality reflects that MSMEs have successfully provided employment opportunities for the local community. The pandemic, which transformed nearly every sector, has also impacted business entities, including Pisang Kapik MSMEs. Pisang Kapik enterprises demonstrated resilience during this period by leveraging technology for banana chip marketing. Through applications such as Go Food and digital communication via Facebook, Google, YouTube, and mobile applications, they successfully penetrated new markets in the digital realm. This adaptation highlights the strategic role of Pisang Kapik MSMEs in navigating the challenges posed by the pandemic and utilizing technology for effective marketing. Keywords: Development, MSMEs, Covid 19, Bukittinggi.